Information Technologies in the Formation of Foreign Language Grammatical Competence While Teaching a Language for Specific Purposes - Labinska, Bohdana; Zenia, Liubov; Matiichuk, Kvitoslava; Danylovych, Oksana (My University, 2021)
Although different aspects of grammatical competence and information technologies have been researched quite thoroughly, the issue of integrated application of information technologies to form foreign grammatical competence for future lawyers during their independent work remains lacking. To fill in the gaps regarding literature, this research paper was designed to present the experience of the teachers of the Foreign Languages Department gained during the COVID-19 pandemic period. The current study aims at demonstrating the effectiveness of the virtual learning environment Moodle in the formation of English language grammatical competence of students during their independent work. The study had a quasi experimental research design with a pre-test and delayed post-test. It was carried out at the Faculty of Law of Yuriy Fedkovych Chernivtsi National University, Ukraine. The participants were fifty 3rd -year students of specialty “International Law,” who took part in the survey voluntarily during the fall semester of 2020- 2021. The core question of the research is whether this learning tool is effective in forming students’ foreign language grammatical competence. Based on the results of the study, the researchers demonstrate the benefits of studying through the electronic system Moodle. Students increased their ability to understand grammatical constructions in professionally oriented texts. To conclude, the findings obtained in this study can be implemented both in online and blended learning for university students during their independent work while working over English for Specific Purposes.
Keywords: electronic system Moodle, English for Specific Purposes, grammatical competence, independent work, International Law students, professionally-oriented texts